Thermal conductivity of cement-based honeycomb materials: A comparative analysis of T-Shaped vs. H-shaped structural designs - Silong Wang; Junxiang Hu; Yuan Gao; Youjian Zhang; Xiaoxuan Gao; Qiangru Shen; Yanming Liu; Jing Chen (Case Studies in Thermal Engineering)
The operational phase of buildings accounts for the majority of their carbon emissions throughout their lifecycle, with heating and cooling systems being the primary contributors. To mitigate this, there has been growing interest in strategies focused on reducing energy consumption, particularly through the optimization of insulation materials. In previous research, we developed a lightweight, high-strength segmental honeycomb support structure and investigated its thermal conductivity and heat transfer mechanisms. Our findings demonstrated excellent thermal insulation performance, highlighting the critical role of pore shape and distribution in optimizing the thermal conductivity. Building upon this work, the present study explores the thermal performance of two cement-based honeycomb materials: T-shaped and H-shaped. Using infrared thermography experiments, we compared the temperature distribution of specimens along the X and Y axes under similar thermal conditions. The results indicated that, at equivalent distances from the heat source, the T-shaped structure exhibited lower temperatures than the H-shaped structure, suggesting superior insulation performance. Further, we utilized Comsol software to simulate heat transfer in both T-shaped and H-shaped structures, which provided insights into the heat transfer mechanisms of each configuration. Based on these findings, we explored various design modifications to the T-shaped structure, focusing on the optimization of flange and web dimensions. This iterative design process led to the identification of an improved T-shaped configuration with enhanced thermal insulation properties. These advancements in the design and optimization of cement-based honeycomb materials represent a significant step toward the development of more efficient insulation materials.